A indiferença aos livros e à leitura: discursos e emoções - Lima, Pamela Sthefani do Amaral Lopes (Universidade Federal de São Carlos, 2025)
This Undergraduate Thesis was developed under the supervision of Professor Luzmara Curcino and is situated within the field of discourse studies. It is linked to the Laboratory for Reading Studies (LIRE–CNPq/UFSCar) and aligns with the group’s broader objective of analyzing discourses on reading that currently circulate in contemporary society. More specifically, it draws on principles that describe the functioning of the “order of discourse,” with particular attention to one of the emotions that shape contemporary relationships between subjects and reading, namely indifference toward books and reading.This work is part of the larger research project coordinated by my advisor and entitled “Pride, Shame, and Other Affects: An Analysis of Emotions in Discourses on Reading,” supported by CNPq – the National Council for Scientific and Technological Development (process 305682/2022-9). The aim of this study is to investigate, in discourses about reading and in representations of Brazilian readers, the evocation of the emotions of “indifference” or “lack of interest” toward books and reading, based on texts published in major newspapers, in order to understand the meaning effects that impact subjects’ relationships with the universe of reading. The data that constitute the corpus of this thesis were collected from the digital archives of the newspapers “O Estado de S. Paulo” (Estadão) and “O Globo”. These texts belong to different editorial genres and were published between 2000 at 2024.The search combined the following keywords: Brazilian reader/reader/reading/books and indifference; Brazilian reader/reader/reading/books and lack of interest. This analysis is grounded in principles and concepts from Discourse Analysis, especially Michel Foucault’s The Order of Discourse, as well as studies dedicated to discourse analysis on reading, articulated with research on emotions, as developed by Luzmara Curcino (2020; 2022) and other members of LIRE. Through this analysis, we seek to understand the extent to which indifference, apathy, and lack of interest appear in texts that address the topic of reading. The central objective is to problematize indifference not merely as an absence of reading, but as an affective-discursive regime that tensions cultural and educational policies, as well as the subjectivities of those who do or do not have access to reading and books, contributing to the debate concerning the guarantee of the right to reading in contemporary society.
Indifference to books and reading: discourse and emotions
Keywords: Discurso; Leitura; Emoções; Indiferença; Desinteresse; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA; 10. Redução das Desigualdades; 4. Educação de Qualidade